Lysophosphatidic Acid Induces Apoptosis of PC12 Cells Through LPA1 Receptor/LPA2 Receptor/MAPK Signaling Pathway - Zhang, Jie; Li, Yiyi; Wang, Chao; Wang, Yaya; Zhang, Yangyang; Huang, Liqin; Zhang, Zhaohui (Frontiers in Molecular Neuroscience, 2020)
Lysophosphatidic acid (LPA) is a small extracellular signaling molecule, which is elevated in pathological conditions such as ischemic stroke and traumatic brain injury (TBI). LPA regulates the survival of neurons in various diseases. However, the molecular mechanisms underlying LPA-induced neuronal death remain unclear. Here we report that LPA activates LPA1 and LPA2 receptors, and the downstream MAPK pathway to induce the apoptosis of PC12 cells through mitochondrial dysfunction. LPA elicits the activation of ERK1/2, p38, and JNK pathways, decreases the expression of Bcl2, promotes the translocation of Bax, and enhances the activation of caspase-3, resulting in mitochondrial dysfunction and cell apoptosis. This process can be blocked by LPA1 receptor antagonist and LPA2 receptor antagonist and MAPK pathway inhibitors. Our results indicate that LPA1 receptor, LPA2 receptor and MAPK pathway play a critical role in LPA-induced neuronal injury. LPA receptors and MAPK pathways may be novel therapeutic targets for ischemic stroke and TBI, where excessive LPA signaling exist.